Challenges for the Church Today in Facing the Negative Influence of Liberal Theology - Wilson Lambertus Situmorang; Rogate Artaida Tiarasi Gultom; Dapot Damanik (Tinta Emas Institute, 2025)
In the development of digital technology today, it has positive and negative impacts on all aspects of human life in the modern era, including in terms of the development of basic understanding of theology related to faith. Easy access to various information including understanding theology is felt as one form of positive impact but is also followed by negative impacts. In the midst of such a phenomenon, today's churches that still have the standard of teaching the word of God based on the traditions of the early Church and the testimony of the apostles' faith face a new, quite serious challenge, namely the widespread spread of teachings about liberal theology which has a bad and negative impact on the growth of the congregation's faith. Liberal theology is an approach in Christian theology that seeks to adapt religious teachings to the development of modern thought, including rationalism, historical criticism, and science. This approach emphasizes the importance of personal experience and reason in understanding the Christian faith, often reinterpreting traditional doctrines to suit the context of the times. For example, doctrines such as the virgin birth, the physical resurrection of Jesus, and miracles are often interpreted symbolically or allegorically in liberal theology.